Fuzzy Decision-Based Optimal Energy Dispatch for Integrated Energy Systems With Energy Storage - Gao, Qiang; Zhang, Xiaodi; Yang, Mixia; Chen, Xianqing; Zhou, Hongqing; Yang, Qiang (Frontiers in Energy Research, 2021)
The integrated energy system is an important strategic direction in the world's future energy field, which will become the main carrier form of the energy future of human society in the next 30-50 years, directly affecting or even determining the future energy strategy pattern of the world. There are many types in the integrated energy system. In the study of optimal dispatching of energy storage, the integrated energy system is modeled according to the energy transmission characteristics of the integrated energy system, which mainly includes the combined cooling, heating and power system and the multi-type energy storage system containing electricity and heat storage. Then, a two-tier optimal scheduling model for an integrated energy system with multiple types of energy storage as the core is established, divided into the day-head scheduling layer and the real-time dispatch layer. At the day-head scheduling layer, an optimization model has been proposed with the minimum cost of the optimization goal and the power network, heating network, cooling network, energy storage operation constraints and carbon constraints as constraints. Then at the real-time dispatch layer, utilize the fuzzy controller to dispatch and control the electric storage system and the thermal storage system. Finally, the verification simulation experiment is carried out in an industrial park. Besides, the energy efficiency, economy and environmental performance before and after the integrated energy system connected to the multi-energy storage device are compared and analyzed, and different scheduling methods are used to compare and prove the advantages of the scheduling method.